Kleeblattschädel skull presenting in concert with Pfeiffer syndrome - Mir Ibrahim Sajid; Noor Malik; Samira S. Balouch; Gohar Javed (Egyptian Journal of Neurosurgery, 2019)
Abstract Background Kleeblattschädel skull, also known as the cloverleaf is a complex synostosis which presents with an enlarged tri-lobar skull resulting temporal bulging and a flat posterior skull, a rare find in the population. This pansynostosis is associated with other congenital syndromes which include Crouzon, Pfeifer, and Carpenter’s. The genetic disorder Pfeiffer syndrome results from skull bones’ premature fusion characterized by deformities of the hand and feet. The author reports a 10-month-old girl who presented with a tri-lobar skull and wide toes which is a significant finding of Pfeiffer syndrome. Case presentation A 10-month-old girl presents with congenital obstructive hydrocephalus due to cloverleaf skull with horizontally enlarged head and large fontanelles. The child also had mid-facial hypoplasia and pre-axial bilateral lower limb polydactyly. Wide toes were also observed, an indicator of Pfeiffer’s Syndrome. Computed tomography (CAT) scans grossly abnormal craniofacial appearances, with premature closure of the sagittal suture giving a cloverleaf skull appearance. There was also a significant thinning of the brain parenchyma. Conclusion Premature closure of sutures leads to a forced growth in a plane perpendicular to the closed suture. Cloverleaf deformity can present with multiple syndromes such as Pfeiffer’s. This leads to gross alteration of the skull with potential underlying morbidity.